Ovarian Abscess Following Therapeutic Insemination - Bradford A. Kolb; Lane Mercer; Albert J. Peters; Ralph Kazer (Hindawi Limited, 1994)
Background: Artificial insemination is a commonly performed procedure for the treatment of various forms of infertility. Infectious complications have only rarely been noted as a complication of intrauterine insemination (IUI).